Sleep Disturbance among Primary School Children as a Result of the COVID-19 Lockdown (Texas Journal of Medical Science, 2022)
A significant portion of the world's population saw significant disruptions in their sleep patterns because of the COVID-19 lockout. The objectives are to assess differences in reported sleep patterns and disruptions in men and women, to evaluate the sleep disturbances in male and female, and to study the association between male and female sleep disturbance and their demographic characteristics.